Immune Cell-Associated Protein Expression Helps to Predict Survival in Muscle-Invasive Urothelial Bladder Cancer Patients after Radical Cystectomy and Optional Adjuvant Chemotherapy - Helge Taubert; Markus Eckstein; Elena Epple; Rudolf Jung; Katrin Weigelt; Verena Lieb; Danijel Sikic; Robert Stöhr; Carol Geppert; Veronika Weyerer; Simone Bertz; Astrid Kehlen; et al. (Cells, 2021)
Bladder cancer (BCa) is the tenth most commonly diagnosed malignant cancer worldwide. Although adjuvant chemotherapy following radical cystectomy is a common therapy for muscle invasive bladder cancer patients, no applicable biomarkers exist to predict which patients will benefit from chemotherapy. In this study, we examined three immune cell markers, the chemokine CC motif ligand 2 (CCL2), the pan macrophage marker cluster of differentiation 68 (CD68) and the M2 macrophage marker cluster of differentiation 163 (CD163), using immunohistochemistry to determine their predictive value for the chemotherapy response in different nodal stage (pN0 vs. pN1 + 2) and tumor stage subgroups (pT2 vs. pT3 + 4). The prognosis was studied in terms of the overall survival (OS), disease-specific survival (DSS), and recurrence-free-survival (RFS) in 168 muscle invasive BCa patients. Chemotherapy was associated with a poorer prognosis in patients with a higher expression of the immune markers CCL2 (RFS), CD68 (DSS and RFS), and CD163 (DSS and RFS) in the N0 group and with poorer survival in patients with a higher expression of the immune markers CCL2 (OS, DSS, and RFS), CD68 (OS, DSS, and RFS), and CD163 (OS, DSS, and RFS) in the pT2 group when compared with treatments without chemotherapy. In contrast, chemotherapy was associated with a better prognosis in patients with a low expression of the immune markers CCL2 (DSS and RFS), CD68 (OS, DSS, and RFS), and CD163 (OS) in the N1 + 2 group. In addition, chemotherapy was associated with improved survival in patients with a low expression of the immune marker CD68 (OS and DSS) and there was a trend for a better prognosis in patients with a low expression of CD163 (OS) in the pT3 + 4 group compared to patients not treated with chemotherapy. Interestingly, CD68 appeared to be the most applicable immune marker to stratify patients by the outcome of chemotherapy in the nodal stage and tumor stage groups. Overall, we suggest that, in addition to the clinical factors of tumor stage and nodal stage, it is also meaningful to consider the abundance of immune cells, such as macrophages, to better predict the response to chemotherapy for BCa patients after radical treatment.